THEORETICAL AND METHODOLOGICAL ASPECTS OF STRATEGIC STATE REGULATION OF THE DEVELOPMENT OF THE NATIONAL ECONOMY IN THE COORDINATES OF SUSTAINABLE DEVELOPMENT - Yatsykovskyy, B.; Chynchyk, A.; Holubka, S.; Yaremchuk, S.; Buriak, Ie. (My University, 2021)
The current state of the Ukrainian economy shows that the process of developing and implementing an effective development strategy is very important, as Ukraine’s economic development strategy is one of the most important documents characterizing the long-term goals and directions of Ukraine’s social development — economical development, development achievement. It should be noted that in European countries such a strategy is given more attention and is very detailed. The article examines the strategic vision of sustainable socio-economic development of Ukraine until 2030. It demonstrates the reform of the values of the people of Ukraine in order to achieve a balance between economic, social and environmental development. The development of the domestic economy is one of the priority tasks in the transformational conditions of our country. Ukraine must become a country with a strong economy and innovative innovations. This requires, first of all, restoring macroeconomic stability, ensuring sustainable economic growth through pro-environmental actions, creating favorable conditions for economic activity and creating a transparent tax policy. The goals of sustainable development are studied, namely: fight against poverty and hunger, good health, quality education, gender equality, good sanitation and clean water, renewable energy, decent work and economic growth, innovation and infrastructure, reducing inequality, sustainable urban development and communities, responsible consumption, combating climate change, preserving marine and terrestrial ecosystems, peace and justice, and partnering for sustainable development. A study of Ukraine’s place in international rankings, analysis of the dynamics of the main indicators of Ukraine’s global competitiveness index, the dynamics of Ukraine’s economic freedom index for 2019—2020. Twelve categories of economic freedom in Ukraine corruption — 154, freedom of taxation — 100, public spending — 161, freedom of establishment — 111, freedom of the labor market — 146, monetary freedom — 184, freedom of trade —54, freedom of trade — 54, freedom of investment — 165, financial freedom — 160. The results should determine the share of each of the four groups in the index of economic freedom
ТЕОРЕТИКО-МЕТОДОЛОГІЧНІ АСПЕКТИ СТРАТЕГІЧНОГО ДЕРЖАВНОГО РЕГУЛЮВАННЯ РОЗВИТКУ НАЦІОНАЛЬНОЇ ЕКОНОМІКИ В КООРДИНАТАХ СТАЛОГО РОЗВИТКУ
Keywords: sustainable development; economy; index; competitiveness; strategy; national; development